PEMBUATAN DAN UJI MUTU FISIK SEDIAAN BODY LOTION PATI BENGKUANG (Pachyrhizus erosus L.). - Taufiq; Andi Idrus Andriawan (Jurnal Kesehatan Yamasi Makassar, 2025)
Body lotion is a skin moisturizing cosmetic that is included in the emollient (softener) group, has moisturizing properties and is easy to apply to the skin. Body lotion can be made from plants, one of which is yam tubers. A study has been conducted with the aim of making and testing the physical quality of yam starch body lotion preparations (Pachyrhizus erosus L.). This research method was carried out using experimental research, namely making body lotion preparations from yam starch (Pachyrhizus erosus L.). Body lotion preparations from yam starch (Pachyrhizus erosus L.) were made with variations in concentration F0 (base), F1 3%, F2 5%, F3 7%. Evaluation of body lotion preparations includes organoleptic tests, homogeneity tests, pH tests, and spreadability tests. The results of the study showed that yam starch can be made into body lotion preparations that meet physical quality including organoleptic tests, namely white in color, distinctive aroma, slightly thick in shape and soft in texture. The body lotion preparation was mixed homogeneously and had an average pH value of 6, and an average spread of 6.4 cm.